THE IDENTIFICATION AND DIFFERENTIATION BETWEEN NORMAL AND SECONDARY COLORECTAL CANCER IN HUMAN LIVER TISSUE USING X-RAY INTERACTION TECHNIQUES - Darvish, Molla Sahar (My University, 2012)
As secondary colorectal liver cancer is the most widespread malignancy in patients with colorectal cancer, the main aim of this study is to identify and differentiate between benign and malignant secondary colorectal liver cancer tissue. Low energy X-ray interaction techniques were used. XRF and coherent scattering data were collected for all 24 normal and 24 tumour matched pair tissues. Measurements of these parameters were made using a laboratory experimental set-up comprising a Mo X-ray tube, Si Drift detector and Scintillation (NaI) detector.
Twelve elements of interest were statistically explored for normal and tumour samples. Comparing normal and tumour tissues, statistically significant differences have been determined for K, Ca, Cr, Fe, Cu, Zn, Br and Rb. However, for P, S, As and Se, no statistically significant differences have been found.
Coherent scatter profiles were collected and fitted for all the samples and three peaks were observed at momentum transfer values: adipose peak: 1.1 nm-1, fibrous peak: 1.6 nm-1 and water content peak: 2.2 nm-1. The Amplitude, FWHM and area under these peaks were statistically analysed. These parameters were found to be significantly higher in secondary colorectal liver tumour compared to surrounding normal liver tissue for both fibrous and water content peaks. However, no significant differences were found for adipose peak parameters.
Multivariate analysis was performed using the XRF, coherent scatter and elemental ratios data separately and the accuracy of classification results of 20 unknown samples was found. However when all the variables were combined together, the classification models were improved. This study has shown that the XRF and coherent scatter data of normal and secondary colorectal liver cancer are statistically different and the combination of these variables in multivariate analysis has the potential to be used as a method of distinguishing normal liver tissue from the malignant tumour tissue.
Keywords: XRF; Coherent Scatter; Normal tissue; Tumour tissue; Trace elements; Multivariate analysis; PCA; SIMCA; Medical Biophysics; Medical Biophysics